2017
DOI: 10.1371/journal.pone.0177444
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of genome editing activity from Natronobacterium gregoryi Argonaute (NgAgo) in human cells

Abstract: The argonaute protein from the thermophilic bacterium Thermus thermophilus shows DNA-guided DNA interfering activity at high temperatures, complicating its application in mammalian cells. A recent work reported that the argonaute protein from Natronobacterium gregoryi (NgAgo) had DNA-guided genome editing activity in mammalian cells. We compared the genome editing activities of NgAgo and Staphylococcus aureus Cas9 (SaCas9) in human HEK293T cells side by side. EGFP reporter assays and DNA sequencing consistentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 31 publications
1
30
0
2
Order By: Relevance
“…Editing activity in human cells with TtAgo has not yet been published. Although a different Ago from Natronobacterium gregoryi , NgAgo, was initially reported to edit DNA in eukaryotic cells at physiological temperatures 38 , these results were questioned 3941 and the original paper was subsequently retracted. If an Ago-based system can be shown to have reliable cleavage efficacy at DNA target sites in eukaryotic cells, a key potential advantage is that, unlike CRISPR–Cas9, there is no requirement of a protospacer adjacent motif (PAM) which would, in theory, make any DNA targetable for editing.…”
Section: Genome Editing Systems — Not Just Cas9mentioning
confidence: 99%
“…Editing activity in human cells with TtAgo has not yet been published. Although a different Ago from Natronobacterium gregoryi , NgAgo, was initially reported to edit DNA in eukaryotic cells at physiological temperatures 38 , these results were questioned 3941 and the original paper was subsequently retracted. If an Ago-based system can be shown to have reliable cleavage efficacy at DNA target sites in eukaryotic cells, a key potential advantage is that, unlike CRISPR–Cas9, there is no requirement of a protospacer adjacent motif (PAM) which would, in theory, make any DNA targetable for editing.…”
Section: Genome Editing Systems — Not Just Cas9mentioning
confidence: 99%
“…Подобный белок мог бы оказаться особенно эффективным при работе с одноклеточными организмами или в клеточных культурах. К сожалению, активность белка не подтверж-дена независимыми исследованиями других лабораторий (Burgess et al, 2016;Javidi-Parsijani et al, 2017;Khin et al, 2017). Белок Аргонавт впервые упоминается в работе, опи-сывающей мутацию Arabidopsis thaliana.…”
Section: аргонавтunclassified
“…Сразу несколько групп начали разрабаты-вать методы геномного редактирования с использованием нового фермента. Неожиданностью стало то, что ни одной группе исследователей не удалось показать его активность (Burgess et al, 2016;Javidi-Parsijani et al, 2017;Khin et al, 2017).…”
Section: аргонавтunclassified
“…The halophilic Argonaute from Natronobacterium gregoryi (NgAgo) was recently put forth as a promising candidate for pAgo-mediated gene editing as it is believed to operate at mesophilic (~37°C) temperatures 20 . However, these claims have since been refuted due to an inability to demonstrate in vitro DNA cleavage or to replicate these findings in a number of eukaryotic hosts 2125 . NgAgo expression is poor, presumably due to its halophilic characteristics that make low salt expression challenging 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…NgAgo expression is poor, presumably due to its halophilic characteristics that make low salt expression challenging 26,27 . Thus, all published in vitro cleavage assays have relied on refolded protein 2125 , which may be non-functional, resulting in the inconclusive results. Nonetheless, recent work by Fu and colleagues demonstrated that NgAgo may still have potential as a gene editor for prokaryotic hosts.…”
Section: Introductionmentioning
confidence: 99%